The fundamentals of business intelligence - what it does and why it's so essential - McDonald, Michael (Henry Stewart Talks, 2017)
What is business intelligence (BI), Using BI, Steps in BI, Advantages and disadvantages of BI, Advanced / predictive analytics, Text analytics